Effect of restrictive versus liberal red cell transfusion strategies on haemostasis: systematic review and meta-analysis - Colman, K; Prick, B; Duvekot, J; Sweeney, C; Odutayo, A; Jairath, V; Doree, C; Trivella, M; Hopewell, S; Estcourt, L; Stanworth, S; Desborough, M (Schattauer, 2017)
Red cells play a key role in normal haemostasis in vitro but their importance clinically is less clear. The objective of this meta-analysis was to assess if correction of anaemia by transfusing red cells at a high haemoglobin threshold (liberal transfusion) is superior to transfusion at a lower haemoglobin threshold (restrictive transfusion) for reducing the risk of bleeding or thrombotic events. We searched for randomized controlled trials in any clinical setting that compared two red cell transfusion thresholds and investigated the risk of bleeding. We searched for studies published up to 19th October 2016 in The Cochrane Central Register of Controlled Trials, MEDLINE, PubMed, Embase, and the Transfusion Evidence Library and ISI Web of Science. Relative risks (RR) or Peto Odds Ratios (pOR) were pooled using a random-effect model. Nineteen randomized trials with 9852 participants were eligible for inclusion in this review. Overall there was no difference in the risk of any bleeding between transfusion strategies (RR 0.91, 95% confidence interval [CI] 0.74 to 1.12). The risk of severe or life-threatening bleeding was lower with a restrictive strategy (RR 0.75, 95% CI 0.57 to 0.99). There was no difference in the risk of thrombotic events (RR 0.83, 95% CI 0.61 to 1.13). The risk of any bleeding was not reduced with liberal transfusion and there was no overall difference in the risk of thrombotic events. Data from the included trials do not support aiming for a high haemoglobin threshold to improve haemostasis.